A regra de exclusão das empresas estatais da lei de recuperação e de falência brasileira - Mendonça, Vinícius de Carvalho Pires (2019)
This dissertation presents the current understanding about the exclusion rule of state-owned enterprises of the Reorganization and Insolvency Law (2005) at the doctrinal and jurisprudential levels in Brazil. In this line, it delimits the legal characters of the public enterprise and the mixed-economy company and the legal treatment applicable to its subsidiaries and to minority state holdings. It expounds in an analytical way how foreign law and jurisprudence have solved the insolvency crisis of companies under public control in comparative law. It analyzes the legal arguments and systematizes the three legal theories about the total exclusion rule of state-owned enterprises of the Brazilian Bankruptcy Law: (i) favorable to exclusion; (ii) partially favorable to exclusion; and (iii) not favorable to exclusion, based on the interpretation of constitutionality, partial unconstitutionality and total unconstitutionality of the insolvency immunity rule. It analyzes the Brazilian jurisprudence on the matter. Finally, it presents the most appropriate legal solution for the crisis of insolvency of state-owned enterprises, based on the harmonization of their social objectives and private interests related to Brazilian reorganization and bankruptcy proceedings